2019
DOI: 10.3390/nu11071475
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Serum Magnesium Levels and Depression in an Adult Primary Care Population

Abstract: Depression is common, places a large burden on the patient, their family and community, and is often difficult to treat. Magnesium supplementation is associated with improved depressive symptoms, but because the mechanism is unknown, it is unclear whether serum magnesium levels act as a biological predictor of the treatment outcome. Therefore, we sought to describe the relationship between serum magnesium and the Patient Health Questionnaire (PHQ, a measure of depression) scores. A cross-sectional analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
1
15
1
2
Order By: Relevance
“…Finally, we identified two studies conducted on healthy populations, evaluating the correlation between magnesium levels and depressive symptoms. Specifically, Tarleton et al (2019) [ 64 ] considered Patient Health Questionnaire (PHQ) scores in a large cohort of 3604 healthy adults and showed a significant relationship between serum magnesium and symptoms. Similarly, Salehi-Pourmehr et al (2019) [ 65 ], who conducted a study on overweight pregnant women, also reported a positive significant correlation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we identified two studies conducted on healthy populations, evaluating the correlation between magnesium levels and depressive symptoms. Specifically, Tarleton et al (2019) [ 64 ] considered Patient Health Questionnaire (PHQ) scores in a large cohort of 3604 healthy adults and showed a significant relationship between serum magnesium and symptoms. Similarly, Salehi-Pourmehr et al (2019) [ 65 ], who conducted a study on overweight pregnant women, also reported a positive significant correlation.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the research carried out on depression highlighted the linked between the development of this disabling illness and reduced plasmatic levels of magnesium, evidence that is line with previous reviews and meta-analyses [ 25 ]. In the light of these results, several studies [ 54 , 56 , 64 ] suggested that, for adults seen in primary care, lower serum magnesium levels were associated with depressive symptoms, ultimately supporting the use of supplemental magnesium as a therapy. For this reason, magnesium could be considered a hallmark of pathology or could represent a biomarker of response to drug treatment in patients with mood disorders, as also reported by a previous review [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to meta-analyses, both insufficient dietary magnesium intakes [182,183] and low magnesium biological status [184] are associated with a higher risk of depression. For example, a recent study in 3600 subjects with a mean age of 62 years observed that those with a high serum magnesium were less likely to be depressed [185]. In a review of observational studies comparing magnesium status in a total of 559 subjects suffering from Alzheimer disease, a lower magnesium concentration in the cerebrospinal fluid was found, when compared with 381 healthy matched controls [186].…”
Section: Intake or Status In Vitamin C Iron Magnesium And Zinc And mentioning
confidence: 99%
“…In human studies, there is some evidence for Mg 2+ deficiency occurring more commonly in MDD patients. However, the effects are heterogeneous ( Serefko et al, 2013 ; Yary et al, 2016 ; Wang et al, 2018 ; Górska et al, 2019 ; Sun et al, 2019 ; Tarleton et al, 2019 ). On the other hand, chronic Mg 2+ supplementation appears to improve MDD symptoms even without a prior diagnosis of Mg 2+ deficiency ( Tarleton et al, 2017 ).…”
Section: Trace Minerals and Mdd-riskmentioning
confidence: 99%